2007
DOI: 10.1037/1064-1297.15.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy and pharmacology influence the subjective effects of nicotine in a balanced-placebo design.

Abstract: The expectancy and pharmacological effects of nicotine (0.60 mg) on memory and the subjective effects of cigarettes were examined using a balanced-placebo design (i.e., expect either nicotine or no nicotine and receive either nicotine or no nicotine). A total of 120 college students who smoke were assigned to 1 of the 4 experimental groups and rated the cigarettes on a number of dimensions and completed questionnaires on smoking urges, tension, and energy. Participants also completed tests of memory as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
50
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 29 publications
(53 reference statements)
10
50
1
1
Order By: Relevance
“…Interestingly, one PET study found that negative drug prediction errors (i.e., alcohol expected but not delivered) decreased striatal DA concentrations while positive drug prediction errors (i.e., alcohol not expected but delivered) increased striatal DA levels in individuals with alcohol dependence (21), which is consistent with our finding of modifiable striatal responses by beliefs. Furthermore, our findings extend previous results showing the impact of beliefs on behavioral performances and subjective states related to nicotine intake (15)(16)(17)20) by detailing the specific neural and computational mechanisms underlying the impact of beliefs on drug effects. These selective effects demonstrate that belief can modulate model-based parameters important for learning and suggest that belief serves as an important cognitive mechanism in addiction.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, one PET study found that negative drug prediction errors (i.e., alcohol expected but not delivered) decreased striatal DA concentrations while positive drug prediction errors (i.e., alcohol not expected but delivered) increased striatal DA levels in individuals with alcohol dependence (21), which is consistent with our finding of modifiable striatal responses by beliefs. Furthermore, our findings extend previous results showing the impact of beliefs on behavioral performances and subjective states related to nicotine intake (15)(16)(17)20) by detailing the specific neural and computational mechanisms underlying the impact of beliefs on drug effects. These selective effects demonstrate that belief can modulate model-based parameters important for learning and suggest that belief serves as an important cognitive mechanism in addiction.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, six parameters generated during motion correction were entered as covariates. In the first GLM, market value r t was entered as parametric regressors at the fifth regressor (market price reveal of rounds [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; in the second GLM, reward prediction error TD t was entered as parametric regressors at the fifth regressor (market price reveal of rounds 2-19). Regressors were orthogonalized in a standard SPM8 fashion.…”
Section: Behavioral Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome expectancies reflect anticipated consequences of smoking (Brandon, 1994;Brandon et al, 1999;Cohen, McCarthy, Brown, & Myers, 2002;Cox & Klinger, 1988;Niaura, Goldstein, & Abrams, 1991) and include beliefs about positive reinforcement (e.g., "I enjoy the taste sensations while smoking"), negative reinforcement/negative affect reduction (e.g., "Smoking helps me calm down when I feel nervous"), negative consequences (e.g., "The more I smoke, the more I risk my health"), and appetite control (e.g., "Smoking helps me control my weight"; Brandon & Baker, 1991). Outcome expectancies are related to key aspects of smoking behavior (Kelemen & Kaighobadi, 2007). For instance, smokers who smoke at higher rates tend to endorse more positive expectancies about the effects of smoking (Ahijevych & Wewers, 1993;Copeland, Brandon, & Quinn, 1995;Downey & Kilbey, 1995), whereas expectancies for negative reinforcement/negative affect reduction predict greater rates of smoking cessation failure (Wetter, Smith et al, 1994).…”
mentioning
confidence: 99%
“…Whether an individual's expectancy for alcohol translates to similar expectancies for cigarette smoking is unclear. However, smoking expectancies are predictive of smoking behavior (Kelemen & Kaighobadi, 2007), and, specifically, negative reinforcement expectancies have been found to predict greater rates of smoking-cessation failure (Wetter et al, 1994). If alcoholic typologies that favor relief drinking (e.g., Type B alcoholics) also favor relief smoking, this may have predictive value in smoking-cessation outcomes with or without concurrent medication treatment.…”
mentioning
confidence: 99%